WAR IN UKRAINE: RUSSIAN PROPAGANDA THEMES - DRUGĂ, Dana Ionela (Strategic Impact, 2023)
With this article, we aim to identify the propaganda themes associated with the Russian Federation in the context of the war in Ukraine and how they are formulated, based on an analysis of the articles found in the database of EUvsDisinfo (Disinfo Database) over a two-month period (August ̶ September 2022). Propaganda themes were identified by applying two types of research: qualitative (content analysis and thematic analysis) and quantitative. The research results indicated the following Russian propaganda themes: the theme of the Zaporozhye nuclear power plant attack, the theme of Nazism and fascism, the theme of military aggression, the theme of Russian values and legality (referendum), the theme of lost sovereignty and imperialism, the theme of staging attacks/massacres, the theme of the global conspiracy and the West, the theme of the food crisis/food insecurity, the theme of Russian minority and Russophobia. The purpose of this analysis is to increase awareness regarding Russian Federation’s hostile actions in the virtual space, as well as the resilience of users to online messages.